NILAI-NILAI MORAL DAN PENDIDIKAN DALAM NOVEL 99 CAHAYA DI LANGIT EROPA KARYA HANUM SALSABIELA RAIS DAN RANGGA ALMAHENDRA - Siti Mukhlisah (LPPM UNISDA, 2017)
This study aims to determine Moral Values ​​and Education contained in novel 99 Cahaya di Langit Eropa works Salsabiela Rais Hanum and Rangga Almahendra using the theory of the moral values ​​of Burhan Nurgiyantoro. The method used is descriptive method. The technique used to analyze the data is to analyze the Moral Values ​​and Education contained. Based on the results, it can be concluded many provide inspiration and motivation to the reader through Moral Values ​​and Education contained therein. Moral values ​​contained in the divided into two types, namely the moral good and bad morals. Moral good cover; social, moral and ethical, pious, diligent study and work, is able to control myself, and regret. Bad moral value include; intrigue, conflict, and lie. Educational value contained in 99 novel Light in the skies of Europe is a faith education, education amaliah (deeds), scientific education, moral education, and education sosial.